2002
DOI: 10.1074/jbc.m201514200
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Reacts with the Single-electron Reduced Active Site of Cytochrome c Oxidase

Abstract: The reduction kinetics of the mutants K354M and D124N of the Paracoccus denitrificans cytochrome oxidase (heme aa 3 ) by ruthenium hexamine was investigated by stopped-flow spectrophotometry in the absence/presence of NO. Quick heme a reduction precedes the biphasic heme a 3 reduction, which is extremely slow in the K354M mutant (k 1 ‫؍‬ 0.09 ؎ 0.01 s ؊1 ; k 2 ‫؍‬ 0.005 ؎ 0.001 s ؊1 ) but much faster in the D124N aa 3 (k 1 ‫؍‬ 21 ؎ 6 s ؊1 ; k 2 ‫؍‬ 2.2 ؎ 0.5 s ؊1 ). NO causes a very large increase (>100-fold) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
5
19
0
Order By: Relevance
“…The rapid inhibition of the oxidase by NO also suggested that it may bind an intermediate in the catalytic cycle unavailable to oxygen, making it a more effective inhibitor than predicted thermodynamically by allowing it to ''outcompete'' oxygen kinetically (41). Nevertheless, we suggested that the steady-state inhibition constants observed in vivo are broadly consistent with simple equilibrium NO binding to the same enzyme intermediate as oxygen binds, namely, the fully reduced binuclear center (7,42).…”
supporting
confidence: 52%
“…The rapid inhibition of the oxidase by NO also suggested that it may bind an intermediate in the catalytic cycle unavailable to oxygen, making it a more effective inhibitor than predicted thermodynamically by allowing it to ''outcompete'' oxygen kinetically (41). Nevertheless, we suggested that the steady-state inhibition constants observed in vivo are broadly consistent with simple equilibrium NO binding to the same enzyme intermediate as oxygen binds, namely, the fully reduced binuclear center (7,42).…”
supporting
confidence: 52%
“…4 we present an alternate reaction scheme for the high electron flux process that we think satisfactorily accounts for the observations from all laboratories. The present work and that of others clearly support a marked preference of NO for the heme site in variously prepared derivatives, and in transient kinetics experiments the inhibited state is thought to be associated with the formation of nitrosylferroheme a 3 (5,16). Therefore, in the chain of events where NO enters the active site pocket before O 2 , the available evidence strongly suggests that it will bind to heme a 3 (I).…”
Section: Discussionmentioning
confidence: 64%
“…4 [16], the relative concentration of reduced intermediates (R and E) tends to rise at higher reduced cytochrome c concentrations, whereas intermediates P and F prevail at lower concentrations. Interestingly, the half-reduced intermediate E seems to react with NO [37]. Thus at higher reductant concentration, reduced cytochrome a 3 is the primary target with formation of a stable nitrosylated adduct (a 3 2+ -NO), whereas at lower reductant concentration, Cu B 2+ is the target and the nitrite derivative (a 3 3+ NO 2 -Cu B 2+ ) is formed.…”
Section: Discussionmentioning
confidence: 96%